KONSELING PENDIDIKAN SEBAGAI SARANA PENGEMBANGAN GROWTH MINDSET SISWA: TELAAH LITERATUR TEORETIS DAN PRAKTIS - Akbar, Sika Raemif; Sri Hidayati (As-Sulthan Journal of Education, 2025)
This article aims to comprehensively examine the role of educational counseling in fostering students' growth mindset through a literature study approach. Growth mindset, a psychological concept introduced by Carol Dweck, refers to the belief that intelligence and abilities can be developed through effort, strategy, and perseverance. In the educational context, this mindset influences how students respond to challenges and failures in the learning process. This study employs a literature review method with a descriptive qualitative approach, analyzing various national and international academic references. The results of the review show that educational counseling holds great potential in facilitating the shift in students’ mindsets from fixed to growth. Through various strategies such as solution-focused brief counseling, cognitive behavioral therapy, and process-based reinforcement, educational counseling can serve as an effective medium in shaping a positive and resilient learning mentality. This review recommends the integration of counseling services and the growth mindset approach within the education system to face 21st-century challenges more adaptively and comprehensively.